(untitled) (Scientific journal of the Fergana State University, 2024)
With the extensive expansion of information technologies, internet addiction among the younger generation emerges as a critical issue, diminishing their cognitive and social potential. This article aims to present an analysis of publications that explore how internet interaction affects children’s psyche in the context of academic achievements and their successful participation in PISA studies. Research indicates the prevalence of internet addiction and its excessive use for entertainment rather than educational purposes, adversely impacting psychological well-being, including among Uzbek students. It concludes that fostering digital literacy among students, educators, and parents is essential. Such measures will ensure successful participation in PISA studies and lay the groundwork for nurturing a resilient, healthy, and educated society capable of adapting to rapidly changing global conditions.